PENGEMBANGAN DESA WISATA MELALUI PELATIHAN GROWTH MINDSET, MANAJEMEN KEUANGAN, DAN DIGITAL BRANDING - Viq Robi Ahmad Wardani; Anisa Handayani; Mohammad Khasan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
This community service activity was carried out in Kandangmas Village, Kudus Regency, with the aim of increasing the community's capacity to develop the potential of the Logung Dam's artificial tourism. The main problems facing this village include limited innovation, weak financial management of BUMDes (Village-Owned Enterprises), and a lack of digital promotion strategies. To address these challenges, the activities were designed through three forms of training: growth mindset, financial management, and digital branding. The implementation method used a participatory approach through workshops, guided group discussions, and hands-on practice. The results of the activities showed that growth mindset training was able to encourage the community to be more innovative in identifying and developing tourism potential; financial management training improved BUMDes' ability to record and prepare financial reports transparently and accountably; and digital branding training equipped Karang Taruna with skills in promoting tourism through social media. Overall, this activity strengthens the synergy between Pokdarwis, Karang Taruna, and BUMDes as the three pillars of tourism management, while also building the foundation for developing Kandangmas Village as an innovative, professional, and sustainable tourism village.